Reasons for Non-Reporting Violence Against Women and Children in Reception and Asylum Centers in Serbia - Jovanović, Slađana (Zbornik Instituta za kriminološka i sociološka istraživanja, 2018)
The author presents the factors for non-reporting violence against women and children in reception centers and asylum centers in Serbia, as evidenced by the results of recently conducted empirical research organized by NGO Atina. Reports of the European Commission, the US Department of State, the Ombudsman of the Republic of Serbia, as well as from non-governmental organizations indiquate the presence of gender-based violence in the migrant/refugee population in Serbia (from 2015 to date). The violence has not been recognized and/or not reported, and there has been an absence of adequate state response regarding the obligation to protect victims and sanction the perpetrators (in accordance with international legal requirements and recommendations). Victims of trafficking in human beings have not been identified, and domestic violence has not been reported, blaming the victims themselves (for they wouldn’t or may not speak about their own victimization). Such an approach has been burdened with prejudices related to diversity in cultural and religious patterns, and often relies on the "best intentions" of those who should act in accordance with international and national legal provisions that do not make a difference between the domestic population and the migrant one when it comes to protection against violence.